Researching inside police custody in four jurisdictions: ‘Getting in’, ‘getting on’, ‘getting your hands dirty’ and ‘getting through it’ - Skinns, Layla (Criminology & criminal justice, 2023)
As a unique criminal justice organisation, the police present challenges, but also opportunities for those who research them. These are examined, in terms of getting in, getting on, getting your hands dirty and getting through it, using data collected as part of a comparative multi-method study of police custody in large cities in Australia, England, Ireland and the United States in 2007 and 2009. As this research took place on the cusp of the proliferation of research with the police, retrospective examination of field notes is used to reflect on how the research process is influenced not just by one’s social origins but also by the culture of academia and the politics of knowledge production. It is argued that while research with the police is becoming the norm, research on the police is still of value as part of a diverse police research agenda.